Руйнування клітин водорості спіруліни за допомогою електрогідроефекту - Голодний, І. М. (Energy and Automation, 2017)
UDK 621.31DESTRUCTION OF CELLS SPIRULINA ALGAE BY ELEKROGIDROEFFKTAІ.M. GOLODNYI, Ph.D (Tech) Annotation. The results of studies on the use of hydro-electric effect cell disruption spirulina algae in the preparation of concentrated nutrients.Key words: algae, vitamins, minerals, hydro-electric effect, a capacitor, a transformer, electrodes, high voltage, disintegration. In general, the technology for concentrated all drugs are as follows: preparation of raw materials; disintegration; obtaining pigments, vitamins, trace elements; drying; packaging.The most promising raw material for drugs is concentrated algae. In particular, the algae Spirulina is an ideal source of protein 60...70%, B vitamins, three pigment (phycocyanin, chlorophyll, carotenoids), trace elements. The very high-protein spirulina vitamin-mineral culture with a wide range of biological activity. Used as a preventive and therapeutic agent for hypo- and beriberi to improve immunity, immunological and metabolic processes. When the additive in animal feed and poultry increased growth by 10 ... 15% survival poultry 4,5...5%.The use inefficient methods of processing algae hinders the development of new technologies in obtaining concentrated preparations.Review of recent studies in this area are detailed in the work [1], where the author also described the results of theoretical and experimental studies on the use of freezing cells for destruction spirulina algae during its processing.In addition, special attention should electrohydraulic effect for food concentrates. Electro-treatment, in which the hydraulic liquid emerging powerful waves, pulsed magnetic fields, ultrasound and intense light emission, cavitation, causing damage to the cell structure of plant and animal tissues, and the damaged cell is 60 ... 90% [2]. The principle of operation of such a facility next. The current from the mains voltage of 380 V is supplied to step-up transformer, which blocks built straighteners. DC piled on the covers of pulse capacitors to a given potential. Then comes the breakdown of forming air gap and almost simultaneously there was a category between the working electrode, where the technological process of testing materials. Installing tested with positive results in the allocation of the alfalfa plant protein-vitamin complex.Aim of paper - protect the environment and reduce energy costs in obtaining concentrated algal nutrients.Materials and research methods. Research electrohydraulic installation is carried out using the theory fundamentals of electrical engineering and computer statistical analysis of experimental data.Research results. Study of elektrohidroudaru the destruction of cell membranes were conducted on laboratory facility. Setting up of the shaper interval, working chamber, condenser, high-voltage power supply, power cable connection. Generator electrode gap with a spherical surface and attached to the centers. One electrode is fixed motionless, the other has a mechanism that makes it possible to change the distance between the electrodes. The working capacity of 1 liter chamber made of stainless steel. In the cover mounted camera working electrode is insulated from the case. The working electrode has the ability to change the distance to the case where the discharge energy of the capacitor. The high-voltage capacitor has parameters U = 20 kV, C = 0.5 mF. The power supply consists of a voltage regulator RU, intermediate transformer TP1, TP2 transformer high voltage, two high-voltage diodes D, support for limiting charging current, voltmeters low U1 and U2 high voltage. In parallel, the chamber includes a voltage divider with a device for recording of transient discharge capacitor. All nodes are connected to high-voltage laboratory setup shielded cable.To set the operating parameters of the installation, including the size of the working gap between the electrodes, conducted laboratory tests to determine the resistivity paste spirulina. For this, the measuring chamber with a capacity of 0.5 liters paste were installed stainless steel electrodes. In the fed voltage electrodes. In terms of voltmeter and ammeter calculated resistivity suspension. As seen in Figure resistivity paste spirulina to 90% humidity and less than 1 Om×m with increasing moisture resistivity increases. The study was conducted at 20 0C suspension.Small resistivity requires special configuration of the working electrode. To this end his work was installed with access to 5 mm of insulation material and ground cone. This made it possible to increase the working period of up to 10 mm due to concentrated in one direction, the narrower the direction of the electric field. A larger gap makes it possible to increase the operating voltage capacitor discharge and therefore increase energy level.Laboratory studies conducted at electrohydraulic installation low voltage U = 20 kV, capacitor capacitance C = 0.5 mF, forming lf = 5.5 mm and work lr = 10 mm intervals. Transient capacitor discharge occurred in real half 4-5. Thus there is potential for raising efficiency of electrohydraulic installation.Spirulina paste after capacitor discharge examined under a microscope and using a spectrophotometer SF2. The results showed that spirulina cells are destroyed. Various sizes applied energy obtained by changing the amount of discharge of the capacitor CONCLUSIONSResearch has established operating parameters of the installation length formative period of 5.5 mm, the distance between the working electrode 10 mm. This transient discharge capacitor held 4-5 by real half.The dependence of cell disruption spirulina energy capacitor discharge. In the energy discharge capacitor 5 kJ destroyed 80% of the cells spirulina. A further slight increase in damaged cells require a sharp increase in the applied energy.The results of research can be used as inputs for the development of a prototype installation and the development of a mathematical model of the process of processing spirulina.REFERENCES• Golodnyi I. Saving obtain highly concentrated algal nutrients electrotechnologies methods. // Electrification and automation of agriculture. - K.: NAU, 2006. - №4. - P. 24-30. [in Ukrainian].• Polupanov I.Y. Electrotechnology Research methods in agriculture / I.Y. Polupanov, N.A. Zhuravlev // Herald-governmental agricultural science. - K.: South Branch of Agricultural Sciences, 1971. - №11. - P. 25-31. [in Ukrainian].• Atabek G.I. Theoretical Fundamentals Elektrotekhnika. - M.-L .: Energy, 1966 – P. 320 p. [in Russian].• Shamarin Y.E. Choice of input data electrohydraulic install disinfection liquid fraction of manure / Y.E. Shamarin, V.Y. Usov, V.A. Popov, V.A. Muzichenko // Mechanization and electrification of agriculture. - K .: Harvest, 1974.- Vol. 29. - P.93-97. [in Ukrainian].